Physical fitness levels among children in northeast Italy by sex and age group: a comparison with teachers’ assessments and children in other European countries - Toscani, Andrea; Pedersen, Arve Vorland (Frontiers in Sports and Active Living, 2024)
Physical fitness is associated with health-related quality of life, especially among youth. Although schools play an important role in promoting children's physical activity, in Italy the lack of qualified physical education teachers in primary schools may be compromising children's achievement of recommended levels of physical activity. To test that possibility, we measured the physical fitness of 170 children (i.e., 79 boys and 91 girls) 6-10 years old in two schools in Cadore, Veneto, in northeast Italy, using the Physical Fitness Test, a tool developed in Norway and previously used among children there and in Lithuania. Teachers in Italy also assessed their students' physical fitness, and their rankings were correlated with the children's test results. The test battery included nine elements: a standing broad jump, hopping 7 m on both feet, hopping 7 m on one foot, throwing a tennis ball, pushing a medicine ball, climbing wall bars, a 10 × 5 m shuttle run, a 20 m run, and a 6 min Cooper test. Test scores generally increased with age and more steeply among boys than girls, and boys outperformed girls on most items. Children in Italy performed similarly to children in Norway but outperformed ones in Lithuania on nearly every item across sex and age groups. The correlation between teachers' predictions and the actual test results was rather low for boys (.538, p < .001) and even lower for girls (.360, p < .001). Data revealed similar results in physical fitness between the three countries, albeit with some differences for individual items. However, primary school teachers in Italy assessed physical fitness rather poorly, possibly due to their lack of specific academic training in physical education and thus limited perception of physical fitness compared with academically trained physical education teachers. Last, because the procedure for categorizing children by age may significantly affect the results and subsequent between-group comparisons, researchers comparing children in different age groups should report their procedures for categorizing age.